2009
DOI: 10.1590/s0102-311x2009000800013
|View full text |Cite
|
Sign up to set email alerts
|

Cambridge Cognitive Examination: performance of healthy elderly Brazilians with low education levels

Abstract: This study aimed to estimate the quartile distribution on the cognitive assessment of normal elderly with low education as measured by the Cambridge Cognitive Examination (CAMCOG). A sample of 292 elderly (> 65 years of age), screened for dementia and depression, were assessed using the CAMCOG. The CAMCOG scores of normal subjects (n = 206) were stratified according to age (65-69, 70-74, 75-79, > 80) and schooling (illiterate, 1-4, and > 5 years of formal education). Mean age was 72.8 (+/- 3.5) and mean school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…To fulfill the item “b” of the Petersen criteria we assessed the memory performance in the Cambridge Cognitive Examination (CAMCOG) [31]. Because of educational heterogeneity in the sample, normative values suggested by a previous study with 292 elderly subjects in the Alzheimeŕs disease Center of the Federal University of Rio de Janeiro were adopted [37]. Subjects with cognitive performance 1.5 S.D.…”
Section: Methodsmentioning
confidence: 99%
“…To fulfill the item “b” of the Petersen criteria we assessed the memory performance in the Cambridge Cognitive Examination (CAMCOG) [31]. Because of educational heterogeneity in the sample, normative values suggested by a previous study with 292 elderly subjects in the Alzheimeŕs disease Center of the Federal University of Rio de Janeiro were adopted [37]. Subjects with cognitive performance 1.5 S.D.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has reported normative data for older Brazilians in the CAMCOG screened for dementia and depression, including illiterates, and seniors with 1-4 years of education, and ≥5 years (Moreira et al, 2009). However, at present, there is no accuracy data for the older population with lower education.…”
Section: Introductionmentioning
confidence: 99%
“…The scores at the first quartile for the group formed by illiterate and 1–4 years of schooling individuals were 58/62 (aged 65–69 years), 52/63 (aged 70–74 years), 48/67 (aged 75–79 years) and 46/64 (aged >80 years). These results showed that subjects with low education and older age had worse performance on the CAMCOG test …”
Section: Discussionmentioning
confidence: 82%
“…In Brazil, Moreira et al . have evaluated with the CAMCOG the cognitive performance of 292 non‐demented elderly subjects with low educational levels . The scores at the first quartile for the group formed by illiterate and 1–4 years of schooling individuals were 58/62 (aged 65–69 years), 52/63 (aged 70–74 years), 48/67 (aged 75–79 years) and 46/64 (aged >80 years).…”
Section: Discussionmentioning
confidence: 99%